Batas Dunia Tanpa Batas: Telaah Singkat Pemikiran I Made Andi Arsana - Eko Rangga Maulana (Literaksi: Jurnal Manajemen Pendidikan, 2023)
The purpose of this research is to find out the perspective of I Made Andi Arsana from the TEDxUGM youtube channel entitled "Border In A Borderless World". In this study, the researcher used a descriptive method by observing the notes method because the source of the data was obtained by listening to oral narratives. The results of this study explain the borders in a world without borders, this study also mentions that a view is limited to a world without borders, which means that boundaries are important, boundaries must exist, but the boundaries we want are boundaries that interact with each other, not boundaries that unite with each other.Borderless world is a concept where all humans or companies in the world can interact and work together without the limitations of space and time. Many cases have been recorded that conflicts between two regions are caused by boundary problems.